Proactive Recruitment of Frontoparietal and Salience Networks for Voluntary Decisions - Rens, Natalie; Bode, Stefan; Burianová, Hana; Cunnington, Ross (Frontiers in Human Neuroscience, 2017)
There is evidence that neural patterns are predictive of free decisions, but findings come from paradigms that have typically required participants to make arbitrary choices decisions in highly abstract experimental tasks. It remains to be seen whether proactive neural activity reflects upcoming choices for individuals performing decisions in more complex, dynamic, scenarios. In this functional magnetic resonance imaging study, we investigated preparatory neural activity for free decisions compared with instructed decisions in a virtual environment, which more closely mimicked a real-world decision. Using partial least squares analysis, we found that the frontoparietal and salience networks were associated with free choice selection from a time at which decisions were abstract and preceded external stimuli. Using multi-voxel pattern analysis, we showed that participants’ choices, which were decodable from motor and visual cortices, could be predicted with lower accuracy for free decisions than for instructed decisions. This corresponded to eye-tracking data showing that participants made a greater number of fixations to alternative options in free choice trials, which might have resulted in less stable choice representations. These findings suggest that free decisions engage proactive choice selection, and that upcoming choices are encoded in neural representations even while individuals continue to consider their options in the environment.